1982
DOI: 10.1271/bbb1961.46.1255
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, physicochemical properties and biological activities of amicoumacins produced by Bacillus pumilus.

Abstract: Bacillus pumilus BN-103 was found to produce a newantibiotic complexnamedamicoumacin. The antibiotic was isolated from the culture broth by ion-exchange resin and carbon chromatographies. AmicoumacinA was a major componentof the mixture, and exhibited not only antibacterial activity, but also antiinflammatory and antiulcer activities. AmicoumacinB and C showed moderate activity against bacteria, but did not exhibit any pharmacological activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 1 publication
0
31
0
Order By: Relevance
“…These two compounds did not have significant antibacterial activities. The production of amicoumacin A as a major component of a mixture of amicoumacins A, B, and C has already been described in another Bacillus species: B. pumilus AI-77 (10).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…These two compounds did not have significant antibacterial activities. The production of amicoumacin A as a major component of a mixture of amicoumacins A, B, and C has already been described in another Bacillus species: B. pumilus AI-77 (10).…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, it has been reported that amicoumacin A also exhibits anti-inflammatory properties, as well as anti-stress ulcer properties, both of which were detected in a rat model (10). However, its activity against H. pylori, which causes inflammation of the gastric epithelium in humans, was not previously bacterial viability (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Some are toxic to man, such as ochratoxin A and B, which are nephrotoxic and hepatotoxic, respectively [5,6]. On the other hand, several isocoumarins are extremely beneficial: duclauxin has antitumor effects [7], baciphelacin is an antiviral [8], amicoumacins are antibacterial and antiulcer [9,10], while others are diuretics, antihypertensives, and used in the treatment of lymphoedema [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the heterocyclic isocoumarin ring can be found in glycosides [homalicin (1) and dihydrohomalicin (2)] and as amino-acid derivatives of active functional groups such as ochratoxin A (3) [3] and amicoumacin B (4) [4]. The antibacterial and gastric-protection activities of a group of amicoumacins isolated from plant material were especially high [4,5]. This confirmed that research on the design of natural compound analogs that combine an isocoumarin core with an amino acid was important and urgent.…”
mentioning
confidence: 99%